2018
DOI: 10.1249/mss.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

Isotemporal Substitution of Sedentary Behavior and Physical Activity on Function

Abstract: Replacing SB with LPA was linked to a significant improvement in the 400W, but not the other brief functional measures. Mixed doses of LPA and MVPA may add flexibility to interventions targeting reductions of SB in older adults for clinically relevant improvements in physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…Reallocating 30 min/week from SB to MVPA and from LPA to MVPA had beneficial effects on subjective health in older adults, in line with previous research showing that spending 30 min/day on LPA instead of SB improved walking ability in older adults [32]. Our results increased current understanding on the role of reallocating PA in elderly South Koreans.…”
Section: Discussionsupporting
confidence: 89%
“…Reallocating 30 min/week from SB to MVPA and from LPA to MVPA had beneficial effects on subjective health in older adults, in line with previous research showing that spending 30 min/day on LPA instead of SB improved walking ability in older adults [32]. Our results increased current understanding on the role of reallocating PA in elderly South Koreans.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, efforts that target SB as a means to increase LPA is a new behavioral leverage-point that could help us increase overall PA and induce health benefits within the population ( 45 ). A recent study using isotemporal substitution regression modeling to assess the relationship of replacing the amount of time spent in one activity for another showed that replacing 60 min/d of SB with 10 min/d of MVPA and 50 min/d of LPA was associated with significant improvements in physical function ( 49 ). However, there is little evidence to guide SB limiting strategies or LPA promotion activities for older adults ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that step counts are a lightintensity activity and do not capture the full spectrum of physical activity. Therefore another possibility is that though walking regressed from 3 to 6 months, patients engaged in isotemporal substitution with other forms of activity, and so some portion of the continued increase in muscle mass and decrease in fat mass in the intervention group was from reduction in overall sedentary time rather than walking [47]. However, walking is the most common form of physical activity for most dialysis patients [48], and it is not evident that patients would switch their focus to other activities so readily.…”
Section: Discussionmentioning
confidence: 99%